Migrating Extremists - Christian Ochsner; Felix Roesel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We show that migrating extremists shape political landscapes toward their ideology in the long run. We exploit the unexpected division of the state of Upper Austria into a US and a Soviet occupation zone after WWII. Zoning prompts large-scale Nazi migration to US occupied regions. Regions that witnessed a Nazi influx exhibit significantly higher voting shares for the right-wing Freedom Party of Austria (FPÖ) throughout the entire post-WWII period, but not before WWII. We can exclude other channels that may have affected post-war elections, including differences in US and Soviet denazification and occupation policies, bomb attacks, Volksdeutsche refugees and suppression by other political parties. We show that extremism is transmitted through family ties and local party branches. We find that the surnames of FPÖ local election candidates in 2015 in the former US zone are more prevalent in 1942 phonebook data (Reichstelefonbuch) of the former Soviet zone compared to other parties.
Keywords: R23; D72; N94; 330